Adomian and Adomian-Padé Technique for Solving Variable Coefficient Variant Boussinesq System - Sabali, Ahmed J.; Manaa, Saad A.; Easif, Fadhil H. (Science Journal of University of Zakho, 2018)
In this paper, Adomian and Adomian-Padé Technique are used to find approximate solutions for the Variable-Coefficient Variant Boussinesq System, and using Adomian-Padé Technique for Debug (Remove) The Gap (Complex Root).